2018
DOI: 10.1002/2017jc013464
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Barrier Wind Forcing on Heat Delivery Toward the Greenland Ice Sheet

Abstract: A high‐resolution numerical hydrodynamic model of Kangerdlugssuaq Fjord and the adjacent southeast Greenland shelf region was constructed in order to investigate the dynamics of fjord‐shelf exchange. Recent studies have suggested that rapid exchange flows, driven by along‐shelf barrier wind events, are the dominant agent of exchange between fjord and shelf. These events are prone to occur during the winter, when freshwater forcing is minimal and observations of the fjord interior are scarce. Subglacial freshwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 59 publications
1
38
0
Order By: Relevance
“…This domain spans approximately 1,300 km of coastline and corresponds well to the region known for strong barrier flow and gale force winds during winter (Harden et al, ; Moore, ). This is also the region where Straneo et al (), Jackson et al (), and Fraser and Inall () suggested that wind‐driven events take place and contribute to the shelf‐fjord exchange. The two types of wind forcing appears to be equally likely, which indicates that the anomalies are normally distributed.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…This domain spans approximately 1,300 km of coastline and corresponds well to the region known for strong barrier flow and gale force winds during winter (Harden et al, ; Moore, ). This is also the region where Straneo et al (), Jackson et al (), and Fraser and Inall () suggested that wind‐driven events take place and contribute to the shelf‐fjord exchange. The two types of wind forcing appears to be equally likely, which indicates that the anomalies are normally distributed.…”
Section: Resultsmentioning
confidence: 80%
“…During downwelling events anomalously light water was forced off the shelf at depth and embedded within the core of the shelfbreak current. These events may be a source of low‐salinity water to the upper layer of the Denmark Strait overflow plume (Rudels et al, ), facilitate shelf‐fjord exchange (Fraser & Inall, ; Jackson et al, ), and precondition the region offshore of the ice edge for wintertime convection (Våge et al, ). Such redistribution of freshwater along the east coast of Greenland may have large‐scale impacts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Key processes that govern the exchanges of heat, freshwater, and nutrients at the ice/ocean boundary, and the upwelling of deep nutrient-rich ocean waters at the glaciers' margins, include localized plume upwelling driven by the subglacial discharge of ice sheet surface melt at glacier grounding lines (Jenkins, 2011;Xu et al, 2012;Sciascia et al, 2013;Kimura et al, 2014;Carroll et al, 2015;Cowton et al, 2015;Slater et al, 2015) and distributed melting along the glacier face ( Figure 2). The circulation of waters in the fjord is thought to be regulated by a combination of buoyancy (Motyka et al, 2003), shelf-driven (Jackson et al, 2014;Fraser and Inall, 2018), and wind-driven forcings (e.g., Moffat, 2014;Spall et al, 2017). This circulation guarantees a continuous supply of heat to melt ice (see review by Straneo and Cenedese, 2015) and regulates the export of the strongly diluted meltwater (Beaird et al, 2015(Beaird et al, , 2017Jackson and Straneo, 2016).…”
Section: Outlet Glaciers and Glacial Fjordsmentioning
confidence: 99%
“…Other freshwater sources, including surface runoff and submarine glacier and iceberg melting, also contribute to the buoyancy forcing that drives a fjord exchange flow. In addition, wind forcing—both locally within the fjord and remotely on the shelf—can drive energetic fjord flows and vigorous exchange between fjords and shelf ocean (Carroll et al, ; Cowton et al, ; Fraser & Inall, ; Jackson et al, , ; Spall et al, ). These wind events, often associated with atmospheric low pressure systems, are strongest during winter and have a seasonal cycle that is opposite to the seasonality of freshwater forcing (Harden et al, ; Oltmanns et al, ).…”
Section: Climate Setting In Greenlandmentioning
confidence: 99%